Fibromatosis Colli - An Infrequent Case Of Neonatal Neck Mass - Madhusudhan Krishnamoorthy; Ram Kumar Sharma Shanmugam; Shahrul Hitam; Nur Safira Abdul Isa; Khairullah Anuar (Manipal University Press, 2024)
Non-indexed Publication